2013
DOI: 10.1021/nl400437f
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying Method for Large-Scale and High-Performance Silicon Negative Electrodes in Li-Ion Batteries

Abstract: Nanostructured silicon electrodes have shown great potential as lithium ion battery anodes because they can address capacity fading mechanisms originating from large volume changes of silicon alloys while delivering extraordinarily large gravimetric capacities. Nonetheless, synthesis of well-defined silicon nanostructures in an industrially adaptable scale still remains as a challenge. Herein, we adopt an industrially established spray drying process to enable scalable synthesis of silicon-carbon composite par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
162
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(163 citation statements)
references
References 41 publications
1
162
0
Order By: Relevance
“…After HCl treatment, the void space inside and among the CVS nanobeads can be formed, which can better accommodate the huge volume change of Si NPs during the cycling processes. [ 27 ] Figure S1 (Supporting Information) clearly shows that all the translucent CVS nanobeads were well coated by the thin and homogeneous outer carbon coatings and supported by a wellconnected 3D carbon network.…”
Section: Introductionmentioning
confidence: 99%
“…After HCl treatment, the void space inside and among the CVS nanobeads can be formed, which can better accommodate the huge volume change of Si NPs during the cycling processes. [ 27 ] Figure S1 (Supporting Information) clearly shows that all the translucent CVS nanobeads were well coated by the thin and homogeneous outer carbon coatings and supported by a wellconnected 3D carbon network.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Si is a particularly attractive anode material, owing to its high specific capacity of B4,200 mAh g À 1 , excellent material abundance and well-developed industrial infrastructure for manufacturing 16,18 . In the past several years, there has been exciting progress in addressing the issues associated with large volume change (4300%) during lithium insertion and extraction by designing nanostructured Si including nanowires and coreshell nanowires [19][20][21][22] , hollow particles and tubes [23][24][25] , porous materials 26,27 , Si/C nanocomposites [28][29][30] and by using novel binders [31][32][33][34] . One of the remaining issues for Si anodes is the large capacity loss in the first cycle.…”
mentioning
confidence: 99%
“…Jung et al reported a silicon-porous carbon composite, which capacitated scalable production by means of industrially available spray drying process. [53] The composite electrode exhibited superior electrochemical performance of 1956 mAh g À1 at 0.1 A g À1 and still maintained 91% capacity retention after 150 cycles. Xu et al introduced a mesoporous Si/C sphere with well-designed void space.…”
Section: Si-carbon Compositesmentioning
confidence: 93%
“…The carbon matrix can (i) accommodate the volume variation of Si nanoparticles upon charge/discharge procedures; (ii) improve the electronic conductivity of the whole composite; (iii) allow efficient transport of Li ions and electrons among the electrode and electrolyte; and (iv) low cost and convenient manufacture. Multifarious carbon materials with different configuration have been employed to synthesis Si-carbon composite, such as carbon frameworks, [42,52] porous carbon substrates, [10,28,[53][54][55][56][57][58] carbon nanotubes. [59,60] Recently, Xu et al proposed a watermelon-inspired Si/carbon (Si/C) microspheres with ingenious hierarchical buffer structure through a combination of spray drying and CVD method.…”
Section: Si-carbon Compositesmentioning
confidence: 99%
See 1 more Smart Citation